If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -14 = 2y + 7 Reorder the terms: -14 + 5y = 2y + 7 Reorder the terms: -14 + 5y = 7 + 2y Solving -14 + 5y = 7 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -14 + 5y + -2y = 7 + 2y + -2y Combine like terms: 5y + -2y = 3y -14 + 3y = 7 + 2y + -2y Combine like terms: 2y + -2y = 0 -14 + 3y = 7 + 0 -14 + 3y = 7 Add '14' to each side of the equation. -14 + 14 + 3y = 7 + 14 Combine like terms: -14 + 14 = 0 0 + 3y = 7 + 14 3y = 7 + 14 Combine like terms: 7 + 14 = 21 3y = 21 Divide each side by '3'. y = 7 Simplifying y = 7
| 9+4(-3)-7= | | -7(1x-2)=0 | | 12x^2+19x+76=0 | | 14x+23=65 | | 5(x+4)-(x+2)=8x+2 | | 7(6-2x)=56 | | 0.6y+8.2=4.7y | | 2a-5=3a-3 | | 15+2(4)-16= | | -2(2x+9)=-54 | | x-33=15-5x | | 7h+2=3h-10 | | 7x-6=8x | | 7(-2x+7)=49 | | 4x^2-34x+49=0 | | 9p+3=9+8p | | -3+6w=33 | | 5x=3+4x | | 4w=32 | | 4x-10=5x-9 | | 2h+8=5h-7 | | 8y+4=10+2y | | 3x-15=35-2x | | 4+4x=7x+28 | | 4.5(x-4)=1.5(x+4) | | 6z-3=4z+5 | | -3+x=5x-9 | | n+4.09=6.38 | | 3+4+6i= | | 4(27)-2(27)-2(3)= | | 2x-4(x+2)=5(x+21)+69 | | 5y+8=-7-10y |